A Prototype System for Time-Lapse Electrical Resistivity Tomographies - Raffaele Luongo; Angela Perrone; Sabatino Piscitelli; Vincenzo Lapenna (International Journal of Geophysics)
A prototype system for time-lapse acquisition of 2D electrical resistivity tomography (ERT) and time domain reflectometry (TDR) measurements was installed in a test site affected by a landslide in Basilicata region (southern Italy). The aim of the system is to monitor in real-time the rainwater infiltration into the soil and obtain information about the variation of the water content in the first layers of the subsoil and the possible influence of this variation on landslide activity. A rain gauge placed in the test site gives information on the rainfall intensity and frequency and suggests the acquisition time interval. The installed system and the preliminary results are presented in this paper.